(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
In this comprehensive article, the author delves into the intricacies of three distinct variants of the English language: Canadian, Australian, and Indian English. The piece provides a detailed exploration of the unique characteristics, linguistic nuances, and cultural influences that shape these variants. The author begins by highlighting Canadian English, emphasizing its multicultural identity and regional diversity across provinces. Regional differences in accent, vocabulary, and grammar are elucidated, showcasing the amalgamation of British, American, indigenous, and French linguistic elements within Canadian English. Moving on to Australian English, the article captures the essence of its laid-back culture and indigenous influences. Notable linguistic features such as vowel shifts, informal speech patterns, and the pervasive use of diminutives are highlighted. Moreover, the incorporation of indigenous words and colloquialisms enriches the portrayal of Australian English.